Resistivity method-based rock core orientation experimental protocol - Jiahuan He; Zhijuan Tang; Qiang Kang; Jiaqi Wang; Li Wang; Hongyu Yao; Qingxiu Zhang; Xingwang Tian; Hongbin Chen; Linling Zhang (PLoS ONE, 2026)
Restoring core orientation is critical for subsurface characterization but remains challenging as over 99% of cores are obtained through conventional drilling. We propose a novel, non-destructive method based on discrete radial resistivity measurements of full-diameter cylindrical cores. Unlike image-matching techniques, our approach directly correlates azimuthal resistivity values with downhole electrical imaging logs, eliminating the need for specialized software. This method reduces measurement time to less than 8 hours per sample and increases throughput to ~150 samples per operator annually, representing a 3–3.75-fold efficiency gain. Applied to Well ST12, it achieved an orientation accuracy of ±15° in anisotropic reservoirs. Measurement accuracy can also be improved as needed. The technique offers a cost-effective, scalable, and widely applicable solution for orienting conventionally acquired cores, enabling enhanced geological and geomechanical analysis.